2003
DOI: 10.1007/s00534-002-0797-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical treatment of choledochal cysts

Abstract: Biliary cystic disease is uncommon in Asia and very rare in Europe and the Americas. Patients with biliary cysts may present as infants, children, or adults. When patients present as adults, they are more likely to have stones in the gallbladder, common duct, or intrahepatic ducts and to present with biliary colic, acute cholecystitis, cholangitis, or gallstone pancreatitis. With increasing age at presentation, the risks of intrahepatic strictures and stones, segmented hepatic atrophy/hypertrophy, secondary bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
121
0
6

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(129 citation statements)
references
References 22 publications
2
121
0
6
Order By: Relevance
“…However, in our study none of the patients presented with classical triad of choledochal cystic disease. Lipsett et al 16 and Jesudason SR 17 mentioned abdominal pain is most common symptom among pediatric and adult patients. According to Singham 18, abdominal pain in pediatric and adult patients has an incidence ranging from 78% to 90%, jaundice and cholangitis being in 40 to 50%.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, in our study none of the patients presented with classical triad of choledochal cystic disease. Lipsett et al 16 and Jesudason SR 17 mentioned abdominal pain is most common symptom among pediatric and adult patients. According to Singham 18, abdominal pain in pediatric and adult patients has an incidence ranging from 78% to 90%, jaundice and cholangitis being in 40 to 50%.…”
Section: Resultsmentioning
confidence: 99%
“…Lipsett et al 16 reported the classic triad of pain abdomen, jaundice and palpable abdominal mass is seen in less than 20% of the cases. However, in our study none of the patients presented with classical triad of choledochal cystic disease.…”
Section: Resultsmentioning
confidence: 99%
“…protrusion of a focally dilated, intramural segment of the distal common bile duct into the duodenum; IVacombination of intra-and extrahepatic cysts; IVbmultiple extrahepatic biliary cysts; and V -multiple intrahepatic cysts (Caroli disease) 7 . Even though our patient had a biliary type II cyst which, like type III, has a low malignant alteration potential and does not require complete excision 2,3 , in this case optimal approach as in case of type I cysts, i.e. timely radical excision, would reduce further complications 3,4 .…”
Section: Discussionmentioning
confidence: 99%
“…This technique avoids injury to vital structures. Sometimes by injection of normal saline into the cyst wall dissection can be made easy [64]. Finally, before establishing choledochoduodenostomy or choledochojejunostomy the hepatic hilum can be flushed of biliary sludge with normal saline as was done in one of the patients; this will reduce risk of forming hepatobilairy stones from biliary sludge.…”
Section: Treatmentmentioning
confidence: 99%